Toward Flexible and Wearable Embroidered Supercapacitors from Cobalt Phosphides-Decorated Conductive Fibers - Wen, Jianfeng; Xu, Bingang; Zhou, Jinyun (Nano-Micro Letters, 2019)
Wearable supercapacitors (SCs) are gaining prominence as portable energy storage devices. To develop high-performance wearable SCs, the significant relationship among material, structure, and performance inspired us with a delicate design of the highly wearable embroidered supercapacitors made from the conductive fibers composited. By rendering the conductive interdigitally patterned embroidery as both the current collector and skeleton for the SCs, the novel pseudocapacitive material cobalt phosphides were then successfully electrodeposited, forming the first flexible and wearable in-plane embroidery SCs. The electrochemical measurements manifested that the highest specific capacitance was nearly 156.6 mF cm−2 (65.72 F g−1) at the current density of 0.6 mA cm−2 (0.25 A g−1), with a high energy density of 0.013 mWh cm−2 (5.55 Wh kg−1) at a power density of 0.24 mW cm−2 (100 W kg−1). As a demonstration, a monogrammed pattern was ingeniously designed and embroidered on the laboratory gown as the wearable in-plane SCs, which showed both decent electrochemical performance and excellent flexibility. Highlights: 1 The conductive silver-plated nylon yarns fully fit the demand for wearable supercapacitor skeleton, owing to the advantages of high conductivity and flexibility. 2 The computerized programming embroidering technique was firstly applied for realizing standardized batch processing of the flexible supercapacitor skeleton in various patterns. 3 Cobalt phosphides were properly electrodeposited on the conductive embroidery as the pseudocapacitive materials, providing remarkable electrochemical performance.